Studi literatur: Gambaran penerimaan diri penderita diabetes mellitus tipe II - Sopia Marlina; Udin Rosidin; Sandra Pebrianti (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Acceptance of illness among patients with type 2 diabetes mellitus: A Literature study Background: Diabetes mellitus is a chronic disease that is a world health problem. Every year there is an increase in the number of morbidity that can be at risk of complications. DM patients require lifelong management to prevent complications. There is a change in lifestyle that can lead to feelings of hopelessness, so it is very important for sufferers to have an attitude of acceptance of illness. Low acceptance of illness can affect sufferers of poor disease management.Purpose: To describe of acceptance of illness among patients with type 2 diabetes mellitus.Method: Using published narrative artarticle obtained from a database-based search process. The data used are secondary data taken from national and international scientific articles starting from 2010 to 2020. The search engine used is Google Scholar and a database from PubMed. Analyzing keywords according to the topic, “acceptance of disease” OR “acceptance” OR “receiving” AND Diabetes mellitus OR Diabetes mellitus Type II.Results: Finding was 10 articles showed 6 articles with a low level patient's acceptance of their illness which could affect sufferers such as low self-care, poor glycemic control, anxiety, depression, quality of life, emotional aspects and disrupting medication adherence while 4 articles showed high acceptance of illness showing DM management. adequate coping, low depression pressure, adherence to medication, good glycemic control and excellent quality of life.Conclusion: The description of the patient's acceptance of their illness shows the results of all articles that developed and developing countries do not affect the acceptance of illness level. Of the 10 articles, 6 articles showed low acceptance of illness and 4 articles showed high acceptance of illness. Keywords: Acceptance of illness; Patient; Type 2 diabetes mellitus Pendahuluan: Diabetes Mellitus merupakan penyakit kronis yang menjadi masalah kesehatan dunia, setiap tahun mengalami peningkatan angka kesakitan yang dapat beresiko terjadi komplikasi. Pasien DM memerlukan pengelolaan seumur hidup untuk mencegah terjadi komplikasi. Terjadi perubahan pola hidup dapat menimbulkan rasa putus asa sehingga penting sekali penderita memiliki sikap acceptance of illness. Acceptance of illness yang rendah dapat mempengaruhi penderita terhadap managemen penyakit yang burukTujuan: Mengetahui gambaran penerimaan diri penderita Diabetes Mellitus Tipe IIMetode: Menggunakan Narrative review artikel yang terpublikasi yang didapatkan dari proses pencarian berbasis database. Data yang digunakan yaitu data sekunder yang diambil dari artikel ilmiah nasional maupun internasional di mulai dari tahun 2010-2020. Search Engine yang digunakan adalah Google Schoolar dan database dari PubMed. Menganalisis kata kunci yang sesuai dengan topik, “penerimaan penyakit” ATAU “penerimaan” ATAU “menerima” DAN Diabetes Mellitus ATAU Diabetes Mellitus Tipe IIHasil: Dari 10 artikel menunjukan 6 artikel dengan acceptance of illness rendah yang dapat menimbulkan dampak pada penderita seperti rendah perawatan diri, kontrol glikemik buruk, kecemasan, depresi, kualitas hidup, aspek emosional dan menganggu kepatuhan pengobatan sedangkan 4 artikel menunjukan acceptance of illness tinggi menunjukan managemen DM koping adekuat, tekanan depresi yang rendah, patuh pengobatan, kontrol glikemik baik dan kualitas hidup baik.Simpulan: Gambaran tentang Acceptance Of Illness pada Penderita Diabetes Mellitus menunjukan hasil dari semua artikel bahwa negara maju dan berkembang tidak mempengaruhi pada tingkat acceptance of illness. Dari 10 artikel yang didapatkan 6 artikel menunjukan acceptance of illness rendah dan 4 artikel menunjukan acceptance of illness tinggi.